SANKSI GANTI RUGI TERHADAP NOTARIS AKIBAT AKTA YANG DIBUAT DIHADAPANNYA - , Roidoan Manik, Dr. Sutanto, SH., M.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this study was to understand legal relationship between notary and attendant as basic imposition of indemnity sanction and qualification of notary action, which may be sanctioned for indemnity and change in notary deed position as result of imposed indemnity sanction. This study used to write this thesis is normative-legal study. Normativelegal study is a study leading to legal principles, legal norms and legal systematic as normative-legal study, so that the study is based on documentary (library) research to collect secondary data in aspect of law. The results of study found that: first, legal relationship in the made deed between notary and attendant in relation to imposition of indemnity sanction is illegal action. Second, qualification of notary action which may by imposed for indemnity sanction against the made deed is regulated in UUJN if violating prohibition concerning deed making technique regulated in Article 16, Paragraph (12), Article 44, Paragraph (5), Article 48, Paragraph (3), Article 49, Paragraph (4), Article 50, Paragraph (5) and Article 51, Paragraph (4), of UUJN and if it is not regulated in UUJN, the notary can be claimed for indemnity by complying with requirements of illegal action which has been regulated in Article 1365 of Civil Code. Third, if notary has been imposed for indemnity sanction, association with degraded deed position becomes underhand deed or the deed is void for law.